Analysis Psychology Language Of Gender In Public As Interest Communication And Familiar Communication (Pascasarjana Universitas HKBP Nommensen, 2025)
This article aimed to describe the implementation of analysis psychology language of gender in public as interest communication and familiar communication. The method of this article was qualitative description research with debriefing to collect data. The object of this research was students college of Muslim Nusantara Alwashliyah University for especially English education departement. Base on the research conducted and description of the researcher, the result of analysis psychology language of gender in public as interest communication and familiar communication showed the difference between each gender in communication.